Conquering Mountains: The Lived Experiences of Nurse Managers on Their Roles and Functions (Ascendens Asia Singapore – Union Christian College Philippines Journal of Multidisciplinary Research Abstracts, 2023)
IntroductionIn today's context, particularly amidst the pandemic, nurse managers play multifaceted roles encompassing intricate responsibilities.  These encompass ensuring operational continuity, devising strategies, and resource management to aid nurses in addressing pandemic-induced challenges.  The nurse manager's role demands determination and patience, involving tasks such as delivering safe care for COVID-19 patients, managing end-of-life situations, supporting grieving families, alleviating staff anxiety stemming from infection risks, aiding anxious children, and addressing moral dilemmas.  Nurse managers, including head and charge nurses, oversee nursing staff, medical resources, financial allocations, patient and nurse satisfaction, care standards, safety protocols, and hospital objectives alignment.  The nurse manager position transcends mere job designation; it stands as a call to selfless service driven by an inherent commitment to enhancing nursing care despite the challenges.  This study unveiled the lived experiences of nurse managers at Al Khafji National Hospital, Saudi Arabia.  It explored their challenges, strategies, and reflections during the pandemic to contribute to the resilience and sustainability of healthcare services. MethodologyEmploying a qualitative descriptive approach, this study utilizes a phenomenological research design to explore the essence of nurse managers' experiences.  The primary focus is on understanding the challenges they encounter and the strategies they employ to address these challenges.  The study participants comprised seven head nurses who willingly participated and shared their experiences.  Purposive sampling was used, including nurse managers with diverse characteristics and backgrounds. Results and DiscussionFrom the data analysis, four significant themes emerged: "Going the Distance," "Striding on a Muddy and Rocky Trail," "Hiking Poles to Get Through," and "The Beautiful Scenery and a Breath of Fresh Air." These themes encapsulate the journey of nurse managers, from grappling with fears and challenges to finding motivation and fulfillment in their roles. The "Going the Distance" theme underscores nurse managers' acceptance of challenging roles and responsibilities, driven by a commitment to professional growth and service improvement.  Despite initial trepidation, they embraced these roles as opportunities for personal and career development."Striding on a Muddy and Rocky Trail" signifies the perseverance of nurse managers in navigating challenges as they strive to enhance the quality of patient care within the constraints of the pandemic.  It reflects their dedication to patient safety, adherence to standards, and continuous quality improvement. "Hiking Poles to Get Through" illuminates the motivation and sources of strength that sustain nurse managers in their roles.  Their determination to fulfill responsibilities is bolstered by factors such as compensation, support from the administration, and the satisfaction derived from professional growth. "The Beautiful Scenery and a Breath of Fresh Air" encapsulates the sense of accomplishment and fulfillment nurse managers experience as they overcome challenges.  Recognition, professional development, and contributions to hospital objectives provide a sense of purpose and reward. Conclusion and RecommendationsThis study highlights nurse managers' journey through challenges and triumphs, underscoring their commitment to improving patient care and the nursing profession.  Recommendations include:• pursuing advanced education in nursing management,• developing tailored training programs for current and future nurse managers, and• providing comprehensive training for bedside nurses to groom them for future management roles. These efforts can contribute to a resilient and sustainable healthcare workforce ready to tackle present and future challenges.
Keywords: Nurse Manager; Nurse Manager's Roles and Functions; Lived Experiences